Mitigating antibiotic misuse in dairy farming systems and milk value chain market: Insights into practices, factors, and farmers education in Nyabihu district, Rwanda - Blaise Iraguha; Jean Pierre M. Mpatswenumugabo; Methode Ngabo Gasana; Elina Åsbjer (One Health)
The widespread misuse of antibiotics to combat bacterial infections in dairy farming is a global concern contributing to antimicrobial resistance (AMR). To gain insights within small-scale dairy farming, a study was conducted in Nyabihu district of Rwanda from September 2021 to April 2023 to assess practices and factors associated with antibiotic use, investigate antibiotic residues in cow milk and undertake a comprehensive training program to improve quality milk production. A mixed-methods approach, combining cross-sectional and longitudinal intervention studies, involved 42 regular dairy farmers from both open and zero-grazing systems delivering milk to the Union pour la Promotion des Cooperatives des Eleveurs en Nyabihu (UPROCENYA) milk collection center (MCC). Standardized questionnaires and farm interviews were conducted to assess antibiotic use practices while bulk tank milk samples from the same farmers were collected and tested for antibiotic residues using rapid tests over 16 months (8 months before and 8 months after training).Out of 451 bulk tank milk samples tested, 27 samples (6%) contained antibiotic residues, primarily tetracyclines (55.3%) and beta-lactams (44.7%). Before farmers training, 5182.75 l of milk were rejected monthly due to antibiotic residues. Following training, milk rejections decreased to 3192.75 l per month, reflecting 38.35% monthly decrease. However, no statistically significant difference was found by independent t-test (t = 1.441; p = 0.173) between milk rejected before and after training. 97.6% of interviewed farmers reported using antibiotics within six months preceding data collection, with 71.4% primarily used for disease treatment, notably targeting tick-borne diseases (34.0%). Alarming practices included administering antibiotics without referring samples for laboratory examination (100%), disregarding withdrawal periods (88.1%) and administering antibiotics without a veterinary doctor's prescription (85.7%). Factors contributing to these practices included limited farmer’s knowledge on antibiotics, easy access to antibiotics in local agro-veterinary shops, and insufficient veterinary services. Antibiotic-laden milk was used to feed calves (38.6%), consumed at home (26.5%), and sold (12.0%).The observed misuse of antibiotics and disregard for antibiotic withdrawal periods pose significant threats to both milk quality and human health. The authors recommend that dairy farmers prioritize animal health monitoring, seek veterinary advice for disease prevention and treatment and implement biosecurity measures to prevent diseases and thus reduce antibiotic usage. Collaborative efforts among stakeholders are highly recommended to enhance capacity building for dairy farmers and support research initiatives. Furthermore, it is strongly suggested to strengthen regulations on the prudent use of antibiotics within the Rwandan food production system to curb antimicrobial resistance across both animal and human populations.